A greedy heuristic protocol for data collection using mobile base station in wireless sensor network. (11th November 2021) - Krishna, N. Santhana; Pradeepa, K.
Deploying mobile entities in wireless sensor network increases their lifespan manifolds as it is very efficient in handling the energy hole problem. Many methodologies and techniques have been adopted by various past research works to minimise the hotspot formation around the base station. Reducing the formation of hotspot has a direct impact on the longevity of sensor network, so more efforts and focus is laid on this particular research area. In this paper we propose a greedy heuristic protocol for data collection termed as GHPDC which greedily selects the energy rich spots for the mobile base station to sojourn. Apart from this the paper has also proposed a linear programming formulation (LPP) which optimises the base station stopping time which will have a direct impact on increasing the network lifetime. The linear programming formulation considers the residual energy of the sensor nodes to decide on the quantity of time for the base station to sojourn.